Accuracy of Medication Labeling and Its Effect on Patient Safety (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Medication labeling accuracy is a critical factor in ensuring patient safety within all healthcare settings. Errors in labeling whether due to human oversight, printing issues, or system failures can lead to serious adverse drug events, treatment delays, or patient harm. This study explores the significance of accurate labeling, identifies common sources of labeling errors, and examines their effect on patient outcomes. It also provides recommendations to improve labeling accuracy through technology integration and quality assurance systems.